Human adaptation - Nielsen, Rasmus (Henry Stewart Talks, 2009)
Darwin, adaptation and natural selection, Genome-wide analyses of natural selection in humans using comparative data, Genome-wide analyses using population genetic data, Individual genes potentially related to specific adaptations in humans, Adaptionism in human molecular evolution